“Can We Get a Clean Up On Aisle 2?”: How Film Critics Mopped Up the Transgressions of Jenny McCarthy’s Dirty Love - Swain, Sara Ann (Pivot: A Journal of Interdisciplinary Studies and Thought, 2013)
Purposefully tasteless, the 'gross-out' comedy is notorious for its lowbrow predilections for toilet humor, salacious sight gags and sexually explicit jokes. Considered by critics to be the lowest form of entertainment, films of this sort are at best affectionately tolerated while at worst they are coolly dismissed. But no gross-out comedy in recent years has been maligned as mordantly as DIRTY LOVE (John Asher, 2005). This ribald, Rabelaisian romp was penned and produced by its star, Playboy model-turned-comedian Jenny McCarthy. This low budget lightweight was not only a monumental box office blunder, but it also consistently garnered poor ratings across the board. It even won a whopping four Golden Raspberries (“Razzies”) the year of its release. Yet for a film that so few people saw (and enjoyed), it let loose a startling deluge of hostility. The reviews, though scant, all harbored a perceptible, unrivaled rancor. Roger Ebert harangues in The Chicago Sun for example, “DIRTY LOVE wasn’t written or directed, it was committed.” But the film’s merit is beside the point—Ebert betrays the crux of his contention when he adds, “it's painful to see a pretty girl, who seems nice enough, humiliating herself on the screen. I feel sorry for her.” Ebert is just one of many critics to insinuate that the film’s failure is ultimately a failure to keep a safe distance between Jenny McCarthy’s erotically charged centerfold body and her comically charged grotesque body. This paper will examine the popular reviews of DIRTY LOVE and identify the rhetorical strategies, from disgust to pity, condescension, and belittlement that critics have used to contain and disinfect McCarthy’s disruption. In probing the film’s reception then, this paper will lay bare the underlying anxieties that persist about women in comedy, and the mutability of female corporeality more generally’s power to unsettle does not rescue it from the gutter, but in re-positing it as a unique and spirited attempt to illuminate underlying taboos, this paper hopes to acknowledge, reconsider and reassess the film’s radical underpinnings.